ANALISIS BIAYA DAN RASIONALITAS TERAPI PARU OBSTRUKTIF KRONIK DI RSU ANWAR MEDIKA SIDOARJO - Lorensia, Amelia; Jalmav, Marthy Meliana; Yorasaki, Yosy Athaya; Saputra, I Nyoman Dodi; Gitaputri, Putu Aprilya (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
COPD is the main cause of death, and is currently the fifth cause of death in the world. COPD patients experience decreased capacity for quality of life, physical disability and increased costs of living. In COPD patients, the use of more than one drug therapy and long-term use can carry the risk of drug-related problems. The aim is to analyze the costs and rationality of treating COPD exacerbations. The research design was retrospective to determine the costs and description of therapy for COPD patients at RSU Anwar Medika Sidoarjo. The variables are real costs, INA-CBGs rates, severity and treatment therapy. The research sample was inpatients with BPJS insurance who were diagnosed with COPD attacks at RSU Anwar Medika Sidoarjo for January 2019-December 2021, using the total sampling method. The data collection by observing research materials including medical records. Data analysis is descriptive for data analysis and the incidence of drug-related problems (MTO), and the Mann-Whitney test to determine significant differences between real hospital costs and INA CBG'S inpatient rates. The number of respondents involved was 81 people. The highest components of direct costs incurred by COPD patients during hospitalization are hotel room costs and the cost of consumable medical materials. There was no difference in real costs compared to the rates INA-CBG's (p=0.158). The total incidence of MTO that occurred was 83 cases consisting of inappropriate drug selection (19.27%), drugs without indications (66.26%), inappropriate drug combinations (4.81%), indications without drugs (2 .40%), too many drugs for same indication (7.22%).